DIFUSIÓN DE LA CULTURA EN INTERNET: MAPA MUNDIAL DE LAS PLATAFORMAS ONLINE - Dr. Miguel TÚÑEZ LÓPEZ ,Anxela CHILLÓN ÁLVAREZ (Fonseca, Journal of Communication, 2023)
The culture as a defining and identitary asset of a society must be transmitted to stay active and spread to be (re)known and appreciated.